In-situ synthesis of biochar modified PbMoO4: An efficient visible light-driven photocatalyst for tetracycline removal. (December 2021) - Chen, Zhifen; He, Zhengping; Zhou, Miao; Xie, Meilin; He, Tianpei; Zhao, Yunlin; Chen, Xiaoyong; Wu, Yaohui; Xu, Zhenggang
Abstract: For highly efficient photocatalytic remediation of organic pollutants, broad-spectrum light response and effective charge separation are two key goals. To achieve these goals, a novel biochar (BC) modified PbMoO4 composite catalyst was successfully synthesized in situ by combining coprecipitation with pyrolysis treatment of poplar sawdust and the technical feasibility of degradation of tetracycline (TC) with compound photocatalyst prepared from recovered agricultural and forestry residues was preliminarily demonstrated. The characterization demonstrated that the presence of BC narrowed the bandgap, enhanced visible light absorption as well as facilitated charge separation. Three composites (with the mass ratio of PbMoO4 to BC = 1:4; 1:1; and 4:1, respectively) displayed higher activity than pure PbMoO4 . The results showed that the composite with the PbMoO4 to BC ratio of 1:4 exhibited the best photocatalytic activity, for 150 mg L −1 TC the removal rate was 61.0%, and the rate constant was 8.1 × 10 −3 min −1, while the photocatalytic activity of PbMoO4 was 26.0% and 3.9 × 10 −3 min −1 . The reactions in the presence of radical quenchers indicated that holes (h + ) and superoxide radicals (O2 − ) were the dominant active species for photodegradation. In different water matrices, for 150 mg L −1 TC solution the photocatalytic activity of optimal photocatalyst decreased as follows: ultrapure water > artificial sewage > farm sewage > municipal sewage. Moreover, the catalyst exhibited good stability over five cycles. Therefore, BC doped PbMoO4 provides a useful strategy for improving the photocatalytic ability of PbMoO4 -based photocatalysts and offers a promising method for water purification. Graphical abstract: Image 1 Highlights: Using poplar sawdust as biochar source realized the rational application of waste. In situ synthesis enhanced the adsorption and photocatalytic activity of PbMoO4 . Superior electrical conductivity of BC helps transport of photogenerated carrier. BC strengthened the visible light response of PbMoO4 @BC-1. PbMoO4 @BC-1 showed promising visible-light photodegradation for TC degradation.